Deriving a Control-Oriented Model for an Axisymmetric Vehicle With the Power-Law Revolution Nose - Jun Huang; Zhigui Liu; Zhiqin Liu; Qingfeng Wang; Jie Fu (Journal of Aerospace Technology and Management, 2020)
The purpose of this paper is to construct a new general vehicle model as an open fundamental material for the guidance and control research. In this study, parameterized configuration, aerodynamics calculation, control-oriented modeling, stability analysis, and nominal trajectory design are performed for the general vehicle model. First, the aerodynamic configuration is parameterized as an axisymmetric body with a power-law revolution nose. Then, an engineering method considering inviscid flow, base drag and skin friction is used for the aerodynamics calculation, and a control-oriented fitting model of longitudinal aerodynamics is established based on the analysis of the correlation between aerodynamic force and the parameters of Mach number, attack angle, elevator deflection and height. Next, the aerothermodynamic environment prediction of power-law revolution axisymmetric hypersonic vehicle (PRAHV) is discussed, and the nose heating rate formula of PRAHV is established. The stability analysis and nominal trajectory design of PRAHV is performed based on the fitting model and the heating rate formula. The stability analysis shows that both the static stability and dynamic stability of the vehicle are unstable. The nominal trajectory of unpowered longitudinal maneuvering is achieved by the hp-adaptive pseudospectral method, which demonstrated that the availability of the control-oriented model established in this paper. In conclusion, this work provides a fundamental object for further study of vehicle guidance, control, and evaluation.